696. Optimal Duration of Prophylactic Antibiotics in Patients with Cirrhosis and Upper Gastrointestinal Bleeding. (4th December 2021) - Davis, Kristin C; Reulbach, Lindsay; Schrank, John; Ewing, Alex; Johnson, Emily
Abstract: Background: Spontaneous bacterial peritonitis (SBP) is a serious complication of variceal hemorrhage. Guidelines recommend a maximum of seven days of antibiotics after variceal hemorrhage to prevent SBP and reduce rates of rebleeding and mortality. However, studies supporting these guidelines used varied durations of therapy including those with less than seven days. The objective of this study was to determine if less than seven days of antibiotic prophylaxis was noninferior to seven or more days in patients with cirrhosis and variceal hemorrhage. Methods: This was a single-center, retrospective cohort conducted from August 2019 to August 2020 including adult patients who received treatment for variceal hemorrhage and antibiotics for prevention of SBP during hospitalization. Patients were excluded if they were diagnosed with non-variceal hemorrhage, received treatment with antibiotics within 72 hours prior to the variceal hemorrhage, or expired or transitioned to end of life care within 48 hours of hospital admission. The primary outcome was in-hospital mortality. Secondary outcomes included SBP within the first 30 days after variceal hemorrhage, 30-day mortality, 30-day readmission rate, incidence of rebleeding at seven and 30 days, incidence of Clostridioides difficile infection, and intensive care unit and hospital length of stay. Results: 64 patients were included with 45 patients in the less than seven days group and 19 patients in the seven or more days of antibiotic prophylaxis group. In each group, patients were primarily male with a median age of approximately 60 years. There was no difference in the primary outcome of in-hospital mortality between the less than seven days group as compared to the seven or more days group (22.2% vs 0%, p=1). No difference was identified between the less than seven days group as compared to the seven or more days group for any of the secondary outcomes. Conclusion: This study identified no difference in patient-centered outcomes when comparing less than seven days of prophylactic antibiotics to seven or more days in patients with variceal hemorrhage. Less than seven days of prophylactic antibiotics may be a reasonable duration for prevention of SBP. Disclosures: All Authors : No reported disclosures